Why we need to go to Venus: The future of European Venus exploration - Wilson, C; Chassefière, E; Imamura, T; Korablev, O; Baines, K; Titov, D; Aplin, K; Balint, T; Blamont, J; Ferencz, C; Cochrane, C; Ferri, F; et al. (2008)
Venus is the most Earthlike planet we know besides our own, in terms of its size and distance from its parent star. It was probably formed from the same materials as the Earth and Mars, at a similar time - why then has it become so different?To address this key question, a team of 170+ scientists from around the world formulated the European Venus Explorer (EVE) mission proposal to the European Space Agency's Cosmic Vision Programme in 2007. Although it was not chosen in the 2007 selection round for programmatic reasons, it was rated a high priority for the future European Space Science so we take this opportunity to reiterate the science goals which motivated the EVE mission, and to discuss the status of technological and programmatic developments required to address these goals.